2021
DOI: 10.1111/jph.12977
|View full text |Cite
|
Sign up to set email alerts
|

Detection and identification of a 16SrIII‐J subgroup phytoplasma associated with faba bean in Peru

Abstract: Faba bean samples with symptoms of yellowing, dwarfism, shoot proliferation, internode shortening, leaf sprouts and lack of pod and seed production were collected from Huancayo and Chupaca provinces, Junin‐Peru, and analysed to verify phytoplasma presence and identity. After total nucleic acid extraction, the amplification with universal phytoplasma primers, using nested polymerase chain reactions, on the 16S ribosomal gene followed by restriction fragment length polymorphism analysis and sequence analysis all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…The presence of 16SrII-D subgroup phytoplasmas in faba bean has been previously reported in Sudan (Alfaro-Fernandez et al, 2012), Saudi Arabia (AL-Saleh and Amer, 2014; Omar, 2017), and Iran , but phytoplasma infecting faba bean was found belong to the 16SrIII group in Spain (Castro and Romero, 2004) and Peru (Torres Suarez et al, 2021).…”
Section: Table (1): the Incidence Of Phytoplasma On Different Crops D...mentioning
confidence: 64%
“…The presence of 16SrII-D subgroup phytoplasmas in faba bean has been previously reported in Sudan (Alfaro-Fernandez et al, 2012), Saudi Arabia (AL-Saleh and Amer, 2014; Omar, 2017), and Iran , but phytoplasma infecting faba bean was found belong to the 16SrIII group in Spain (Castro and Romero, 2004) and Peru (Torres Suarez et al, 2021).…”
Section: Table (1): the Incidence Of Phytoplasma On Different Crops D...mentioning
confidence: 64%
“…The 16SrIII-J phytoplasma strain is widespread in other countries of South America such as Brazil (Montano et al, 2000), Argentina (Galdeano et al, 2013) and Chile (Quiroga et al, 2020) where it was detected in several herbaceous and woody horticultural species. Recently it was also identified in faba bean in Peru (Torres-Suarez et al, 2021) and insect vectors of this phytoplasma strain were identified as Paratanus exitiosus (Beamer) and Bergallia valdiviana Berg 1881 in Chile (Quiroga et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Phytoplasma has been shown to be associated with the faba bean. The most common symptoms of phytoplasma infections of the faba bean are phyllody, shortening of internodes, flower virescence, witches’ broom, small leaves, and yellowing symptoms [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%